A hospital-based study on lipid profile in acute myocardial infarction in Goa - Menezes, Carlos Noel; Nayak, Aditya Hanuman; Sawant Dessai, Bhargav P.; Mardolkar, Saiesh Madhukar (International Journal Of Community Medicine And Public Health, 2022)
Background: Acute myocardial infarction (AMI) is by far the most important form of ischemic heart disease (IHD). Epidemiological surveys have shown that atherosclerosis due to dyslipidemia is directly correlated with risk of IHD. Methods: A prospective Case series study was conducted among 200 patients who suffered from AMI and admitted at Goa medical college, Bambolim from 1st January 2020 to 31st March 2020. After taking consent, the patient’s socio-demographic details were taken from the patients and blood sample for lipid profile and inflammatory markers estimation was obtained within 24 h from the onset of symptoms. IEC approval taken before conducting the study. Results: The patients were aged between 42 and 80 years (mean 59.51±11.41). They included 140 (70%) males and 60 (30%) females. Most of the patients had suffered from anterior wall MI (51, 25%) inferior (72, 36%) lateral wall (15, 7%) septal 62 (31%). The study found a significant association between longer hospital stay and development of complications post MI among patients with raised serum TG levels and low HDL levels. Conclusions: Our study revealed that with the increase in TG level and decrease in HDL levels, the rate of complications post MI and hospital stay increased which is suggestive that high TG levels and low HDL levels may be a significant marker for post MI. Hence a preventive approach would go a long way to prevent complications.